Supporting Error Chains in Static Analysis for Precise Evaluation Results and Enhanced Usability - Wickert, Anna-Katharina; Schlichtig, Michael; Vogel, Marvin; Winter, Lukas; Mezini, Mira; Bodden, Eric
Context Static analyses are well-established to aid in understanding bugs or vulnerabilities during the development process or in large-scale studies. A low false-positive rate is essential for the adaption in practice and for precise results of empirical studies. Unfortunately, static analyses tend to report where a vulnerability manifests rather than the fix location. This can cause presumed false positives or imprecise results. Method To address this problem, we designed an adaption of an existing static analysis algorithm that can distinguish between a manifestation and fix location, and reports error chains. An error chain represents at least two interconnected errors that occur successively, thus building the connection between the fix and manifestation location. We used our tool CogniCryptSUBS for a case study on 471 GitHub repositories, a performance benchmark to compare different analysis configurations, and conducted an expert interview. Result We found that 50 % of the projects with a report had at least one error chain. Our runtime benchmark demonstrated that our improvement caused only a minimal runtime overhead of less than 4 %. The results of our expert interview indicate that with our adapted version participants require fewer executions of the analysis. Conclusion Our results indicate that error chains occur frequently in real-world projects, and ignoring them can lead to imprecise evaluation results. The runtime benchmark indicates that our tool is a feasible and efficient solution for detecting error chains in real-world projects. Further, our results gave a hint that the usability of static analyses may benefit from supporting error chains.
Keywords: Static analysis; error chains; false positive re- duction; empirical studies

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

Videoanalysen zu unterrichtlichen Lehr- und Lernprozessen unter den Bedingungen der Digitalität an organisational resilienten Schulen in Deutschland - Drossel, Kerstin; Oldak, Anna; Bette, Ricarda; Eickelmann, Birgit; Schreyer, P. (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern[i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi[ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann). Abstract To implement inclusive education successfully, it is crucial that teachers and other school staff are trained to cooperate effectively as a team and to involve parents in educational processes. In the project BiFoKi (Bielefeld Training on Cooperation in inclusive), we developed an in-service training for inclusive schools that addresses the intra-institutional cooperation within schools and the inter-institutional cooperation with the parents of students with and without special educational needs. The training aims to prepare grade-level teams to create a welcoming atmosphere, adapt communication ways to the diverse needs of parents and students and to involve parents more strongly in school educational processes. To evaluate the effectiveness of the training, a quasi-experimental study with a pre-post control group design was implemented. Longitudinal data is available for 55 teachers and other professionals. The results indicate that the intervention group demonstrated a more positive development in terms of satisfaction with parents' willingness to cooperate as well as self-reported cooperative behavior in the area of educational cooperation, compared to the control group.
Keywords: General Medicine

Eine Methode zur Unterstützung von Entscheidungen bei der Entwicklung modularer Leichtbauprodukte - Yang, X.

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Anwendung von System Dynamics zur Geschäftsmodellinnovation in einem B2B-Ökosystem - Ksouri-Gerwien, Christoph; Vorbohle, Christian (Digitale Plattformen und Ökosysteme im B2B-Bereich)

Measuring collective efficacy for inclusion in a global context - Sharma , Umesh; Loreman , Tim; May , Fiona; Romano , Alessandra; Lozano , Caroline Sahli; Avramidis , Elias; Woodcock , Stuart; Subban , Pearl; Kullmann, Harry (European Journal of Special Needs Education)

Belgischer Symbolismus zum Be/Greifen nah. Museumskoffer zum Werk von Léon Spilliaert und George Minne.
Der belgische Symbolismus wurde in den letzten Jahrzehnten neu entdeckt. Während Künstler wie Léon Spilliaert und George Minne lange ein Geheimtipp waren, ziehen sie nun ein großes Publikum in ihren Bann. Dennoch gelten viele Werke dieser Kunstströmung bis heute aufgrund der sie prägenden anspruchsvollen Formensprache, verborgenen Bedeutungen und mystischen Visionen als ebenso anziehend wie unergründlich. Die hier vorgestellten siebzehn Museumskoffer bieten vielfältige Zugänge, sie in ihrem kulturellen und kunsthistorischen Kontext zu entdecken und zu verstehen: Sie machen kulturelles Lernen zu einem ganzheitlichen Erlebnis und öffnen Türen zu neuen Welten. Ergänzend stellt der Katalog Texte zum Medium ‚Museumskoffer‘, zum belgischen Symbolismus und weiteres relevantes Informationsmaterial zur Verfügung.
Keywords: Belgischer Symbolismus; Museumskoffer; León Spilliaert; George Minne